Photovoltaic array reconfiguration under partial shading conditions for maximum power extraction: A state-of-the-art review and new solution method. (15th April 2022) - Rezazadeh, Sevda; Moradzadeh, Arash; Pourhossein, Kazem; Akrami, Mohammadreza; Mohammadi-Ivatloo, Behnam; Anvari-Moghaddam, Amjad
Highlights: Introducing a static-based PV array reconfiguration method called 8-Queen's that has no dependence on PV dimensions and shadow size. Ability to implement the proposed method without the need for sensors and switches in the PV system, which in this regard is cost-effective compared to other conventional techniques. Overcoming the limitations of classical and electrical array reconfiguration methods such as the use of high connections and complex wiring are obvious advantages of the 8-Queen technique. Implementing the proposed method in a short time such as a few microseconds on the PV system. Providing a comparative approach to evaluate the results of the 8-Queen's method with other common methods used to PV array modules reconfiguration. Abstract: Non-uniform irradiance due to partial shading conditions (PSCs) reduces the power delivered by the photovoltaic (PV) cell. The output power reduction in the PV arrays directly depends on the shading pattern and type of array configuration which is selected. So far, many dynamic and static reconfiguration methods have been used for maximum power point tracking under PSCs in the PV arrays. However, most conventional methods suffer from some major problems such as the need for additional equipment and sensors, complex wiring, the use of expensive sensors, production of complex switching matrices, high costs, and inability to reconfigure PV arrays with very small, large, and non-square sizes. Accordingly, this paper, after reviewing the dynamic and static PV array reconfiguration methods, presents a novel static-based technique called 8-Queen's for reconfiguring the PV modules corresponding to the Total-Cross-Tied (TCT) inter-connection PV array. The 8-Queen's technique has a great ability to apply on high dimensions and rectangular shapes PV arrays and is based on the movement of 8 queens on the chessboard so that none of the queens can attack the others. The effectiveness of the suggested method is expressed by implementing it on 7 cases of the TCT PV array in different sizes and various PSCs. In a comparative scenario, the performance and effectiveness of the proposed 8-Queen's technique are evaluated compared to other conventional methods. Indicators of global maximum power point (GMPP), fill factor, power efficiency, and mismatch losses evaluate the results of the employed methods. The evaluation of results represents the effectiveness of the 8-Queen's technique compared to other used methods. In addition, the performance evaluation of the proposed technique in real-world PV arrays is performed by modeling a sample PV array taking into account measurement errors. The results in this step also show that the proposed technique can also provide acceptable performance for solving problems related to maximum power point tracking under PSCs in PV systems.